Library Availability and Usages Statistics among Government and Private Schools of North 24 Pargana District, West Bengal: A Descriptive cum Survey Study (LIS TODAY, 2023)
The present paper briefly discusses on library statistics like availability of library resources,  accessibility by male and female students and problems among government and private schools of  North 24 pargana district, West Bengal by descriptive cum survey method. After study it was found  that each and every private school has library facilities where 35% government school has well set up  library, 20% has moderate library and 30% school don’t have any library facility and it was found  that 95% private school has a librarian where 45% government school don’t have any librarian.  About the library usage among students in private school a huge percentage of students uses library  regular and frequent basis but in government school only 10% students visited library regularly while  45% frequently visited and 21% students don’t use library facilities. Finally a gender divide  (dissimilarity) has been found in usage of library facilities.
Keywords: School library; Library statistics; Government school; private school; Male and Female students; West Bengal